The Role of Organizational Commitment in Mediating the Effect of Knowledge Sharing and Competence on Organizational Citizenship Behavior - Masrum, Muhammad; Akob, Muh; Jumady, Edy (Golden Ratio of Human Resource Management, 2025)
This study aims to examine the effects of knowledge sharing, competence, and organizational commitment on Organizational Citizenship Behavior (OCB) at PT Espri Tirta Kencana. Using a quantitative approach and survey method, the study involved a total of 57 employees as the sample. Data were collected through questionnaires distributed via Google Forms, and analyzed using Partial Least Squares (PLS). The results show that knowledge sharing has a positive and significant effect on OCB, while competence has no significant effect on OCB. Organizational commitment was found to have a positive and significant effect on OCB. Furthermore, organizational commitment mediates the relationship between knowledge sharing and OCB, but does not mediate the effect of competence on OCB. These findings suggest that fostering a culture of knowledge sharing and enhancing organizational commitment can improve OCB within the company. The results also indicate that competence, although crucial for task performance, does not directly influence OCB, highlighting the importance of other factors such as organizational attachment and collaboration.